2010
DOI: 10.1371/journal.pone.0009407
|View full text |Cite
|
Sign up to set email alerts
|

CRY2 Is Associated with Depression

Abstract: BackgroundAbnormalities in the circadian clockwork often characterize patients with major depressive and bipolar disorders. Circadian clock genes are targets of interest in these patients. CRY2 is a circadian gene that participates in regulation of the evening oscillator. This is of interest in mood disorders where a lack of switch from evening to morning oscillators has been postulated.Principal FindingsWe observed a marked diurnal variation in human CRY2 mRNA levels from peripheral blood mononuclear cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 74 publications
9
103
2
Order By: Relevance
“…In addition, currently, there are no published data from Cry2 mutant mice on tests that induce anxiety-like or depressive-like behaviors, or on their alcohol intake. As such, this finding supports the view that CRY2 is clearly a "mood gene", since it is associated with a range of depressive phenotypes, including winter depression, on the basis of major depressive disorder (Lavebratt, Sjöholm, Soronen, et al, 2010), bipolar disorder (Sjöholm, Backlund, et al, 2010), the depressive episode of bipolar disorder (Lavebratt, Sjöholm, Soronen, et al, 2010), a chronic course of depressive symptoms due to major depressive disorder or bipolar disorder (Fiedorowicz, Coryell, Akhter, & Ellingrod, 2012), and dysthymia that is chronic depression (Kovanen, Kaunisto, Donner, Saarikoski, & Partonen, 2013).…”
Section: Anxiety Disorderssupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, currently, there are no published data from Cry2 mutant mice on tests that induce anxiety-like or depressive-like behaviors, or on their alcohol intake. As such, this finding supports the view that CRY2 is clearly a "mood gene", since it is associated with a range of depressive phenotypes, including winter depression, on the basis of major depressive disorder (Lavebratt, Sjöholm, Soronen, et al, 2010), bipolar disorder (Sjöholm, Backlund, et al, 2010), the depressive episode of bipolar disorder (Lavebratt, Sjöholm, Soronen, et al, 2010), a chronic course of depressive symptoms due to major depressive disorder or bipolar disorder (Fiedorowicz, Coryell, Akhter, & Ellingrod, 2012), and dysthymia that is chronic depression (Kovanen, Kaunisto, Donner, Saarikoski, & Partonen, 2013).…”
Section: Anxiety Disorderssupporting
confidence: 80%
“…In a sample of 712 patients with bipolar disorder and 1044 controls, two risk haplotypes and one protective haplotype in CRY2 were identified for bipolar disorder with the feature of rapid cycling (Sjöholm, Backlund, et al, 2010). The study by Lavebratt, Sjöholm, Soronen, et al (2010) demonstrated that CRY2 mRNA expression, as assessed from peripheral blood mononuclear cells at several times during one-night sleep deprivation, was decreased in depressed patients with bipolar disorder, as compared with controls, and that total sleep deprivation did not induce any increase in CRY2 mRNA levels in the non-responsive patients opposite to the change seen in the controls.…”
Section: Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the HSPA1B gene, which does not contain introns, primers were designed to span at least one exon-exon junction using Primer-BLAST (http://www.ncbi.nlm.nih.gov/tools/primer-blast/), or were taken from published literature (Archer et al, 2008;Kimura et al, 2011;Lavebratt et al, 2010;Visser et al, 2011;Wu et al, 2006), and were checked for transcript specificity using the UCSC In-silico PCR tool (http://genome.ucsc.edu/). Primer sequences are given in Supplementary Table S1.…”
Section: Hormone Assaysmentioning
confidence: 99%
“…Several genomic studies support the association between CLOCK genes and depression (Lavebratt et al 2010;Soria et al 2010;Wulff et al 2010;McCarthy et al 2012) and see Wulff et al (2010) for review. A gene-wide test by Soria et al (2010), utilising a large sample of patients with major depressive disorder (MDD) and 209 single-nucleotide polymorphisms (SNPs) covering 19 circadian genes, found significant associations in CRY1 and NPAS2 SNPs in depressed patients versus controls.…”
Section: Chronobiology In Depressionmentioning
confidence: 98%